2019
DOI: 10.3389/fphar.2019.00316
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan and Helicobacter pylori Treatment: A Lesson From Japan or a Limited Geographic Phenomenon?

Abstract: Within a short time after the discovery of Helicobacter pylori , its critical role in many gastroduodenal disorders became evident. Many in vitro and in vivo data have proven that infection should be treated in order to avoid lasting colonization which may lead to problematic gastroduodenal diseases. Probiotics, preventive and therapeutic vaccines and antibiotic therapy are the main options proposed to cure these disorders. 25 years ago, trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
0
21
1
1
Order By: Relevance
“…Moreover, it has been shown that VPZ could increase the eradication rate of triple therapy even in clarithromycin-resistant strains [94]; therefore, it is presumable that VPZ could help the transition of H. pylori from coccoid to spiral shape. However, VPZ is currently available only on the Japanese market, and other confirmatory studies are necessary to assess its potential in Western countries [95].…”
Section: Therapeutic Prospective Optionsmentioning
confidence: 99%
“…Moreover, it has been shown that VPZ could increase the eradication rate of triple therapy even in clarithromycin-resistant strains [94]; therefore, it is presumable that VPZ could help the transition of H. pylori from coccoid to spiral shape. However, VPZ is currently available only on the Japanese market, and other confirmatory studies are necessary to assess its potential in Western countries [95].…”
Section: Therapeutic Prospective Optionsmentioning
confidence: 99%
“…Another peculiarity consists in the rapid onset of the effect: While PPIs usually require more than 75-100 h to achieve the maximal gastric acid inhibitory effect[47,48], VPZ induces a fast, powerful and long-lasting gastric acid inhibition[49]. Therefore, in conclusion, VPZ seems to be better than conventional PPIs for five reasons: (1) It is more potent in acid secretion blockade; (2) It has a fast onset of action; (3) It is less prone to metabolization variables due to cytochrome polymorphisms; (4) Greater safety; and (5) Better tolerability[50].…”
Section: Novel Drugs: a Focus On Vonoprazanmentioning
confidence: 99%
“…Finally, it seems that the effectiveness of this drug could be explained by its best suppression of acid secretion. Nevertheless, these enthusiastic results require to be confirmed by forthcoming studies outside Japan[50].…”
Section: Novel Drugs: a Focus On Vonoprazanmentioning
confidence: 99%
“…In Indonesia, H. pylori infection prevalence is about 22.1%, suggesting H. pylori infects approximately one out of five of the population [ 5 ]. H. pylori infection is significantly correlated with incidences of gastritis, gastroesophageal reflux disease, gastroduodenal ulcers, gastric mucosal-associated lymphoid tissue (MALT) lymphoma, and gastric malignancies [ 6 , 7 , 8 , 9 ]. The eradication of H. pylori is vital in reducing peptic ulcer recurrence, in the principal therapy of gastric MALT lymphoma, and in minimizing the risk of gastric cancer [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%